(3GdMGhj GdcHjQs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s
(3ChdgG (B:s
(3GdcdGe Ydi eSM GdQCS s
(3BNQgG (B:s
(3GdbSe GdQGHY ef GdcdGe Ydi GdMjV s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B298 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B628s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs